2016
DOI: 10.3846/16111699.2015.1101396
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Real Exchange Rates in the Central and Eastern European Countries

Abstract: We investigate the mean reversion in real exchange rates for Central and Eastern European countries. We use point and confidence interval estimates from the Phillips et al. 's (2001) local-persistent model as our preferred measures of the persistence of real exchange rates. We find that the adjustment to purchasing power parity is more rapid after accounting for structural breaks, with half-life deviation from parity below 18 months, which is consistent with the explanation based on nominal rigidities. The es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…In addition, the exchange rate is also widely used to observe the nexus between tourism demand and financial stability (Webber, 2001;Eugenio-Martin, 2004;Santana et al, 2010;Baharumshah et al, 2016). Most of these studies found that a flexible and low exchange rate promotes international tourism demand primarily in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the exchange rate is also widely used to observe the nexus between tourism demand and financial stability (Webber, 2001;Eugenio-Martin, 2004;Santana et al, 2010;Baharumshah et al, 2016). Most of these studies found that a flexible and low exchange rate promotes international tourism demand primarily in developing countries.…”
Section: Introductionmentioning
confidence: 99%